Women, youth and everything else: age-based and gendered stereotypes in relation to digital technology among elderly Italian mobile phone users. (September 2017) - Comunello, Francesca; Fernández Ardèvol, Mireia; Mulargia, Simone; Belotti, Francesca
In the context of an international research project on older people's relations with and through mobile telephony, Italian participants spontaneously provided narrations on mobile phones that appeared to be structured around strong stereotypes. Respondents show a twofold representation of mobile phones either as a simple communication tool or as a 'hi-tech' device, which generates multifaceted stereotypes. More specifically, when the mobile phone is considered as a simple communication tool, age-based stereotypes address younger people's bad manners, while gendered stereotypes depict women as 'chatterboxes' or 'social groomers'. On the other hand, when the mobile phone is considered a 'hi-tech' device, age-based stereotypes underline younger people's advanced user skills, while gendered stereotypes focus on women's lack of competencies. Based on that, we provide a conceptual framework for analysing such stereotyped – and apparently conflicting – representations. Interestingly, while some issues also emerged in other countries, the masculine assumption that women are less-skilled mobile phone users appears as a peculiarity of Italian respondents.